2020
DOI: 10.1186/s40168-020-00833-w
|View full text |Cite
|
Sign up to set email alerts
|

Tapping into the maize root microbiome to identify bacteria that promote growth under chilling conditions

Abstract: Background: When maize (Zea mays L.) is grown in the Northern hemisphere, its development is heavily arrested by chilling temperatures, especially at the juvenile phase. As some endophytes are beneficial for plants under stress conditions, we analyzed the impact of chilling temperatures on the root microbiome and examined whether microbiome-based analysis might help to identify bacterial strains that could promote growth under these temperatures. Results: We investigated how the maize root microbiome compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 53 publications
2
55
0
Order By: Relevance
“…To confirm the results of the soil dataset and to evaluate the differences in metabarcoding methods on samples with reduced diversity, we examined the bacterial communities of a root-related dataset, referred to below as the plant dataset. This dataset contained bacterial sequences of two plant-related compartments, the rhizosphere, i.e., the soil closely surrounding the root, and the endosphere, i.e., the inside of the plant root of field soilgrown maize (Zea mays L.) [24]. Fig.…”
Section: Differences Between Asv and Otu Methods In Plantrelated Bactmentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm the results of the soil dataset and to evaluate the differences in metabarcoding methods on samples with reduced diversity, we examined the bacterial communities of a root-related dataset, referred to below as the plant dataset. This dataset contained bacterial sequences of two plant-related compartments, the rhizosphere, i.e., the soil closely surrounding the root, and the endosphere, i.e., the inside of the plant root of field soilgrown maize (Zea mays L.) [24]. Fig.…”
Section: Differences Between Asv and Otu Methods In Plantrelated Bactmentioning
confidence: 99%
“…To create the culture-based mock bacterial community with 254 bacterial isolates (Table S6 A), maize roots were sterilized and crushed [24]. Diluted suspensions were plated and incubated.…”
Section: Datasets For Culture-based Bacterial and Fungal Mock Communimentioning
confidence: 99%
“…Microbial-based plant biotechnology has been proven to be more effective than plant breeding and genetic improvement methods [ 13 ]. A recent study has shown that endophytes improve plant tolerance against abiotic stresses such as salinity, drought and cold [ 6 , 14 , 15 , 16 , 17 , 18 , 19 ]. PGPB and fungi can alleviate abiotic stresses of their host plants via a variety of mechanisms [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our study site, we carried out a plantation of bare root eucalyptus seedlings (3600 eucalyptus ha -1 ). We selected eucalyptus as the focal crops for our research because eucalyptus is the most prominent pulp and wood material in Guangxi [4]. Bare-root eucalyptus (DH32-29, a clone of Eucalyptus urophylla x E. grandis) seedlings were supplied by Dongmen tree farm, Guangxi, China (seedling quality examination certi cate number 2011-029) and planted using three-dimensional holes (20 cm * 20 cm * 20 cm) for each individual.…”
Section: Experimental Sitementioning
confidence: 99%
“…The utility of bacterial fertilizers has been studied in crops such as maize (Beirinckx et al 2020 (Santos et al 2018). However, to our knowledge, few studies have focused on the effects of sludge and PGPR on forest plantations, as well as on understanding the underlying mechanisms via soil quality alteration.…”
Section: Introductionmentioning
confidence: 99%